SAT0198 A comprehensive behavioral intervention in systemic lupus erythematosus demonstrates improvement in endothelial function, mental health but not in physical health or cardiovascular risks at one year. (23rd January 2014) - Fortin, P.R.; Aghdassi, E.; Cymet, A.; Morrison, S.; Su, J.; Wynant, W.; Pope, J.; Hewitt, S.; Pineau, C.; Neville, C.; Harvey, P.; Tardif, J.-C.; et al.
Abstract : Background: The Health Improvement and Prevention Program (HIPP) in systemic lupus erythematosus (SLE) is the first intervention aimed at improving health status and coping skills of persons with lupus while reducing cardiovascular (CVD) and osteoporotic risk. Objectives: To determine whether HIPP will improve health status, endothelial function and CVD risk at one year. Methods: An unblinded RCT of the HIPP intervention compared to usual care assessed physical (PCS) and mental (MCS) component summary scores of SF-36, CVD risk derived from the Framingham risk score (FRS) and flow mediated dilatation (FMD) of the brachial artery. Patients with SLE and no CVD were recruited from three academic centres. After providing consent, SF-36, disease activity (SLEDAI-2K) and damage (SDI), CVD risk factors and FMD were collected. Those randomized to HIPP NOW were administered a personalized risk modification program by a nurse (disease education, CVD risk reduction including smoking cessation, exercise, psychological intervention). Repeated clinical assessments and FMD were performed at one and two years. A cross-over of the LATER group occurred at one year and all patients were reassessed at 2 years. We report here on the results from both groups one year after the HIPP intervention. Paired t-tests at the Bonferroni-corrected 2-tailed alpha=0.0125 were used to assess the statistical significance of the mean changes, estimated from data pooled across the two trial arms, in the four primary outcomes PCS, MCS, FMD and FRS comparing the one year post HIPP versus baseline data. Results: We randomized 288 patients; one withdrew at baseline leaving 287 for analysis. Mean age was 44 yrs, 70% were Caucasian, 53% married, 91% high school graduates, mean disease duration was 11.3 yrs, mean SLEDAI 4.04 and mean SDI 1.17. Mean FMD increased significantly during the intervention period from 0.33 to 0.344, with mean increase of 0.014 (95% CI: 0.004 to 0.024), p=0.005). Mental health also improved significantly, as mean MCS scores increased from 45.15 to 46.78 with a mean increase of 1.63 (95% CI: 0.62 to 2.65, p=0.002) In contrast, there was no evidence of a systematic change in the PCS with scores of 40.71 pre and 40.61 post HIPP (p=0.80). We observed a significant increase in the FRS, even after eliminating the effect of age. More analyses will be done to determine if the increase in FRS was slower in those who received HIPP immediately compared to those who received it one year later. Conclusions: The HIPP behavioral intervention improved significantly the endothelial dysfunction and mental health of persons with SLE but not the physical health. Cardiovascular risk measured by FRS worsened over that period despite HIPP. We need to evaluate next whether HIPP sufficiently improves endothelial dysfunction to mitigate the effects of the progression in cardiovascular risk. Disclosure of Interest: P. Fortin Consultant for: Roche, GSK, Speakers Bureau: GSK, Actelion, E. Aghdassi: None Declared, A. Cymet: None Declared, S. Morrison: None Declared, J. Su: None Declared, W. Wynant: None Declared, J. Pope: None Declared, S. Hewitt: None Declared, C. Pineau: None Declared, C. Neville: None Declared, P. Harvey: None Declared, J.-C. Tardif: None Declared, M. Abrahamowicz: None Declared, D. DaCosta: None Declared